2006
DOI: 10.1177/000331970605700313
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pseudoaneurysm as a Rare Cause of Superior Vena Cava Syndrome

Abstract: This case is about an aortic pseudoaneurysm after Dacron graft replacement that presented as a rapidly evolving superior vena cava syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The frequent use of central venous cannulations and dialysis catheters has led to increased venous thrombosis with SVC and subclavian obstruction (12)(13)(14). Other cases of SVC syndrome include aortic pseudoaneurysm (5,15) and compressive mediastinal hematoma (16).…”
mentioning
confidence: 99%
“…The frequent use of central venous cannulations and dialysis catheters has led to increased venous thrombosis with SVC and subclavian obstruction (12)(13)(14). Other cases of SVC syndrome include aortic pseudoaneurysm (5,15) and compressive mediastinal hematoma (16).…”
mentioning
confidence: 99%
“…Fukui et al reported a case of SVC syndrome caused by a chronic dissecting aortic aneurysm after aortic valve replacement ( 4 ). Pseudoaneurysms of the ascending aorta or aortic arch -traumatic, infectious or iatrogenic- have been also reported as causes of SVC syndrome ( 5 - 8 ). A rare case of SVC syndrome has been reported in a 8-year old girl as a consequence of long-term use of central venous catheters for hemodialysis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fukui et al reported a case of SVC syndrome caused by a chronic dissecting aortic aneurysm after aortic valve replacement (4). Pseudoaneurysms of the ascending aorta or aortic arch -traumatic, infectious or iatrogenic-have been also reported as causes of SVC syndrome (5)(6)(7)(8). A rare case of SVC syndrome has been reported in a 8-year old girl as a consequence of long-term use of central venous catheters for hemodialysis (9).…”
Section: Discussionmentioning
confidence: 99%